Enhancing Problem-Solving and Self-Directed Learning in 8th-Grade Students through a Problem-Based Learning Approach - Aropiq, Putri Rizki; Nasrullah, Anton; Yendra, Novi (EDUPEDIA Publisher, 2025)
This research aims to assess the effect of the Problem Based Learning (PBL) model on students' problem-solving abilities and learning independence. Motivated by the low problem-solving skills in mathematics, caused by a lack of varied learning models and student inactivity, the study compares students receiving PBL treatment with those undergoing conventional learning. A quasi-experimental method was used, involving a pretest, posttest, and learning independence questionnaire. The study was conducted in the 2023/2024 academic year with 8th-grade students from SMP PGRI Walantaka. Results show that students in the PBL group had significantly better problem-solving abilities compared to those in the conventional group, with a significance level of 0.000 (p < 0.05), indicating the effectiveness of PBL. Additionally, the average learning independence of students was 79%, categorized as good. The findings suggest that PBL can improve both problem-solving abilities and learning independence in mathematics education.